Microbiota from the distal guts of lean and obese adolescents exhibit partial functional redundancy besides clear differences in community structure. (14th August 2012) - Ferrer, Manuel; Ruiz, Alicia; Lanza, Francesca; Haange, Sven‐Bastiaan; Oberbach, Andreas; Till, Holger; Bargiela, Rafael; Campoy, Cristina; Segura, Maria Teresa; Richter, Michael; von Bergen, Martin; Seifert, Jana; et al.
Summary Recent research has disclosed a tight connection between obesity, metabolic gut microbial activities and host health. Obtaining a complete understanding of this relationship remains a major goal. Here, we conducted a comparative metagenomic and metaproteomic investigation of gut microbial communities in faecal samples taken from an obese and a lean adolescent. By analysing the diversity of 16S rDNA amplicons (10% operational phylogenetic units being common), 22 Mbp of consensus metagenome sequences (∼ 70% common) and the expression profiles of 613 distinct proteins (82% common), we found that in the obese gut, the total microbiota was more abundant on the phylum Firmicutes (94.6%) as compared with Bacteroidetes (3.2%), although the metabolically active microbiota clearly behaves in a more homogeneous manner with both contributing equally. The lean gut showed a remarkable shift towards Bacteroidetes (18.9% total 16S rDNA), which become the most active fraction (81% proteins). Although the two gut communities maintained largely similar gene repertoires and functional profiles, improved pili‐ and flagella‐mediated host colonization and improved capacity for both complementary aerobic and anaerobic de novo B12 synthesis, 1, 2‐propanediol catabolism (most likely participating in de novo B12 synthesis) and butyrate production were observed in the obese gut, whereas bacteria from lean gut seem to be more engaged in vitamin B6 synthesis. Furthermore, this study provides functional evidence that variable combinations of species from different phyla could 'presumptively' fulfil overlapping and/or complementary functional roles required by the host, a scenario where minor bacterial taxa seem to be significant active contributors.